A bioeconomy perspective for natural sweetener Stevia. (30th December 2018) - Ciriminna, Rosaria; Meneguzzo, Francesco; Pecoraino, Mario; Pagliaro, Mario
Abstract: The 'sweet herb' ( El Caa‐ehe ), used by the Guaraní tribes living in the forests of today's eastern Paraguay and southern Brazil, is rapidly emerging as a natural sweetener that is an alternative both to sugar and synthetic sweeteners, well beyond Japan where it has been widely used since the mid‐1970s. Stevia rebaudiana (Bertoni) Bertoni contains very sweet steviol glycosides in its leaves, which do not add calories and do not cause an increase in blood sugar levels. The glycoside that is most abundant in the leaves, stevioside, has high reactive oxygen species quenching activity and several properties that are beneficial to health. Rapid advances in green chemistry technology allow the production of stevia extracts that are devoid of any liquorice‐like after taste. Their high chemical and physical stability enables them to be used in baked and beverage food products and this supports the large‐scale use of stevia as a natural sweetener. Addressing bioeconomic aspects ranging from production to product formulation, this study identifies the last obstacles prior to general adoption of S. rebadudiana as a sweetener that is beneficial for health. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd